2022
DOI: 10.1038/s41598-022-25332-w
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric conductive electrospun nanocomposite PCL/Polyaniline/Barium Titanate scaffold for tissue engineering applications

Abstract: Recent trends in tissue engineering technology have switched to electrical potentials generated through bioactive scaffolds regarding their appropriate effects on cell behaviors. Preparing a piezo-electrical stimuli scaffold with high electrical conductivity for bone and cartilage tissue regeneration is the ultimate goal of the present study. Here, Barium Titanate nanoparticles (BaTiO3 NPs) were used as piezoelectric material and highly conductive binary doped Polyaniline nanoparticles (PANI NPs) were synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In some articles, it was observed that the reduction of fibers leads to an increase in piezoelectric properties, so that the voltage output from the fibers increased with the reduction of the fiber diameter [ 28 , 29 ]. In research, Shirazi et al [ 30 ] mentioned that the fiber diameter is inversely related to the d33 piezoelectric coefficient, and individual crystallites of 25 nm in diameter exhibited the highest piezoelectric response. This suggests that smaller fiber diameter may lead to better piezoelectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…In some articles, it was observed that the reduction of fibers leads to an increase in piezoelectric properties, so that the voltage output from the fibers increased with the reduction of the fiber diameter [ 28 , 29 ]. In research, Shirazi et al [ 30 ] mentioned that the fiber diameter is inversely related to the d33 piezoelectric coefficient, and individual crystallites of 25 nm in diameter exhibited the highest piezoelectric response. This suggests that smaller fiber diameter may lead to better piezoelectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was shown that as the ultimate strength increased the elongation at the break point declined. Previous studies have shown that the blending or coating of PANI can increase Young's modulus and ultimate strength [62][63][64]. For instance, in a study, the tensile strength of pure PCL fibrous mats increased from 2.33 MPa to 3.51 MPa as PANI coated on PCL fibers [62].…”
Section: Mechanical Property Assessment Of Pani-coated Patchesmentioning
confidence: 96%
“…CNTs are materials with known chemical, electrical, mechanical, and structural properties, while their combination with PCL improves the electrical conductivity of the resulting composite and induces bone healing ( Peidavosi et al, 2022 ). Carbon nanotubes are often used as imaging agents and carriers of bioactive molecules ( Saito et al, 2008 ; Gonçalves et al, 2016 ; Wesełucha-Birczyńska et al, 2021 ).…”
Section: Pcl-based Compositesmentioning
confidence: 99%